Differences of risk factors and clinical presentations in male and female Taiwanese individuals with Barrett's esophagus. Issue 10 (October 2018) - Lee, Shou‐Wu; Lien, Han‐Chung; Chang, Chi‐Sen; Chang, Chung‐Hsin; Ko, Chung‐Wang; Yeh, Hong‐Zen
Abstract : Background: : Barrett's esophagus (BE) is a disorder more often found in obese men. Differences between the two genders are not known in the Asian countries. Here, we studied their gender differences in the Taiwanese population in terms of risk factors and clinical presentations. Methods: : Data from Taichung Veteran General Hospital were prospectively collected during an approximately two year‐period (October 2012 to December 2014). Patients all underwent endoscopic surveillance, and BE was diagnosed based on the typical pattern of intestinal metaplasia. The patient characteristics were compared between the two genders. Results: : We enrolled 152 BE patients: 103 men and 49 women. We found in the males, when compared with the females, significantly older mean age, higher waist circumference, greater BMI (ratio of obesity BMI ≧25 kg/m 2 ), and more cases with dyslipidemia and hiatus hernia. Long‐segment BE and high‐grade dysplasia/adenocarcinoma appeared only in males. Self‐reported reflux symptoms were noted 80.6% in men and 89.8% in women. In those with dysplastic BE, we found these patients having higher ratios of obesity, hiatus hernia, alcohol drinking, cigarette smoking and reflux symptom. Conclusion: : Gender differences were found in our BE patients, males were older in age, more obese, and suffered more serious signs from BE in terms of both endoscopic and pathologic presentations.